2019
DOI: 10.1097/pcc.0000000000001917
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Virtual Reality Experience in the PICU: A Pilot Study*

Abstract: Objectives: Patients in the PICU frequently have limitations that impede independent interactions with their environment. Virtual reality is an immersive experience that may improve outcomes in critically ill children. The objective of this study was to assess feasibility and satisfaction with virtual reality. Design: Cross-sectional, single-arm pilot study. Setting: PICU. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 21 publications
4
37
1
Order By: Relevance
“…We included six qualitative studies and most (4/6) were conducted with neonatal or pediatric critical care populations. Caregivers were most commonly parents (n = 19, 61%) [ 30 , 31 , 33 , 35 38 , 41 44 , 47 49 , 51 , 52 ] and unspecified family caregivers more broadly—which could include parents, but the term was more broadly defined (n = 7, 23%) [ 23 , 24 , 26 , 27 , 32 , 39 , 50 ]. One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included six qualitative studies and most (4/6) were conducted with neonatal or pediatric critical care populations. Caregivers were most commonly parents (n = 19, 61%) [ 30 , 31 , 33 , 35 38 , 41 44 , 47 49 , 51 , 52 ] and unspecified family caregivers more broadly—which could include parents, but the term was more broadly defined (n = 7, 23%) [ 23 , 24 , 26 , 27 , 32 , 39 , 50 ]. One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ]. Few studies reported additional perspectives from members of the clinical care team (e.g., nurses, primary care physicians) (n = 3, 10%) [ 29 , 34 , 50 ] or critical care patients (n = 3, 10%) [ 22 , 28 , 49 ]. More than half of the studies examined real-time communication platforms (e.g., FaceTime, Skype) (n = 17, 55%) [ 23 , 24 , 28 , 30 40 , 47 , 51 , 52 ], which accounted for many of the studies conducted with adult populations (3/7, 43%) and most of the studies conducted with neonatal or pediatric populations (14/22, 64%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising use is for distraction during painful procedures such as burn dressing changes [ 74 ], lumbar punctures, and blood draws [ 75 ] which results in decreasing the amount of sedative or opiate required to complete the task (T3 level outcomes). Some preliminary studies have explored the association between VR and the ICU experience with results showing the potential for decreasing postintensive care syndrome, mitigating anxiety and delirium from prolonged hospitalizations [ 76 ], and encouraging early mobilization [ 77 ].…”
Section: The Individual Learnermentioning
confidence: 99%
“…Providers and patients who have used VR have overwhelmingly positive experiences to share [1,19,20]. Health professionals currently using VR in practice highlight benefits including flexibility, adaptability, and accessibility of the technology.…”
Section: Introductionmentioning
confidence: 99%